Calculation of ionization in direct-frequency comb spectroscopy - Lomsadze, B.; Fehrenbach, C. W.; DePaola, B. D. (My University, 2012)
Direct-frequency comb spectroscopy (DFCS) is currently the highest-resolution absolute frequency spectroscopic technique known. In general, one does DFCS by scanning the repetition rate, frep, of a comb laser and measuring fluorescence from the excited states of the species under study. The technique has already been successfully characterized by a theoretical model that starts with the optical Bloch equations and, with a few simplifying assumptions converts them into linear coupled iterative equations. In the present work we build on that successful model to predict the characteristics of the ion yield from photoionization by the comb laser, as a function of frep. We show that the ion spectrum yields the same atomic structure as the fluorescence spectra, but with greater efficiency.